The Commons in an Age of Uncertainty: A Review Essay - Ulrich Duchrow (American Journal of Economics and Sociology, 2021)
Franklin Obeng-Odoom's recent work offers an alternative to both conventional economics and to what he calls the "Western left consensus." Obeng-Odoom's option involves placing justice at the center of policy regarding commons, not as a side note. Justice requires a focus on the land issue. This much is true, but Obeng-Odoom ignores the plurality of views that are critical of the dominant political economy. A successful transition to a sustainable future will make use of many cultural and religious traditions working together.
Keywords: 330